Single-strand and ladder-type polymeric acceptors based on regioisomerically-pure perylene diimides towards all-polymer solar cells. (24th January 2019) - Wang, Lei; Hu, Ming; Zhang, Youdi; Yuan, Zhongyi; Hu, Yu; Zhao, Xiaohong; Chen, Yiwang
Abstract: Since dibromo perylene diimides (DBPDIs) contain two isomers that are difficult to separate, isomeric effect on properties and applications of PDI polymers has been rarely studied. Few ladder-type polymers have been used in organic solar cells. Herein, single-strand polymers (PrPDIT) were synthesized by the polymerization of regioisomerically-pure 1, 7-dibromo-PDIs (1, 7-DBPDIs) and 2, 5-bis(trimethylstannyl)thiophene. Furthermore, ladder-type polymers (FPrPDIT) were obtained by the highly efficient photo-induced cyclization of polymers PrPDIT. The effects of isomers and molecular weight on the absorption, electrochemistry, thermal stability, and photovoltaic application of polymers were studied. Pure 1, 7-DBPDIs lead to polymers with molecular weight distribution as low as 1.08. These polymers with strong absorption in 300–700 nm, low-lying lowest unoccupied molecular orbital (LUMO) energy levels around −4.0 eV and high thermal stability could be excellent electron acceptors. Regioisomerically-pure polymers demonstrate better photovoltaic performance than that of mixed ones. The highest power conversion efficiency (PCE) of all-polymer solar cells based on PrPDIT and FPrPDIT is up to 5.95% and 4.52% respectively. Graphical abstract: Regioisomerically-pure 1, 7-DBPDIs lead to single-strand polymers (PrPDIT) with molecular weight distribution as low as 1.08. Ladder-type polymers (FPrPDIT) were synthesized by the quantitative yield cyclization of PrPDIT. Both PrPDIT and FPrPDIT are excellent acceptors with highest power conversion efficiency of 5.95% in all-polymer solar cells.Image 1 Highlights: Regioisomerically-pure 1, 7-DBPDIs lead to single-strand polymers (PrPDIT) with molecular weight distribution as low as 1.08. Ladder-type polymers (FPrPDIT) were synthesized by the quantitative yield cyclization of PrPDIT. Both PrPDIT and FPrPDIT are excellent acceptors with highest power conversion efficiency of 5.95% in all-polymer solar cells.